PRABOWO’S INDEPENDENT ACTIVE FOREIGN POLICY ON PALESTINE AND ITS GLOBAL IMPLICATIONS - Fadlillah, Syafiuddin; Komarudin, Ujang (Universitas Padjadjaran, 2026)
This study discusses the implementation of Indonesia’s free and active foreign policy under President Prabowo Subianto concerning the Palestinian issue and its implications for Indonesia’s global role. The principle of Indonesia’s free and active foreign policy serves as the foundation for determining the direction of its foreign policy, particularly regarding the Israel–Palestine conflict. This research employs a qualitative method using Rosenau’s Foreign Policy Analysis theory to analyze the domestic and international factors influencing Indonesia’s foreign policy decisions, and interviews with experts. The findings indicate that President Prabowo reaffirmed his commitment to Palestinian independence through active diplomacy at the United Nations (UN), the Organization of Islamic Cooperation (OIC), and bilateral meetings with major powers. This policy strengthens Indonesia’s image as a middle power that contributes to global peace, although Indonesia’s strategic position has not yet made it a dominant force in the Asian region. The implications of this policy are evident in Indonesia’s enhanced bargaining position at the international level, its active role in the Islamic world, and the growing global recognition of Indonesia’s position.